2004
DOI: 10.1111/j.1525-1446.2004.21112.x
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Health Practices of Canadian and Jordanian Nursing Students

Abstract: The purpose of this study was to compare health-promoting practices of Canadian (n = 49) and Jordanian (n = 44) first-year nursing students using the revised Health-Promoting Lifestyle Profile II. Results indicated significant differences between the groups on three subscales: health responsibility, physical activity, and interpersonal relations; however, both groups had similarly low scores. Implications for nurse educators are discussed from both curricular and cross-cultural perspective that focuses on heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
46
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(59 citation statements)
references
References 18 publications
11
46
0
2
Order By: Relevance
“…Most of the students (31.2%) were also reported not to be engaged in any form of physical activity, nor did they exercise regularly (13.8%). Similar results were also reported in a study [34] where Canadian and Jordanian student nurses ranked health responsibility the lowest in the sub-scales. Besides, it was also highlighted [33] that male subjects scored better in the physical exercise sub-scale as compared to their female counterparts (p = 0.01).…”
Section: Discussionsupporting
confidence: 77%
“…Most of the students (31.2%) were also reported not to be engaged in any form of physical activity, nor did they exercise regularly (13.8%). Similar results were also reported in a study [34] where Canadian and Jordanian student nurses ranked health responsibility the lowest in the sub-scales. Besides, it was also highlighted [33] that male subjects scored better in the physical exercise sub-scale as compared to their female counterparts (p = 0.01).…”
Section: Discussionsupporting
confidence: 77%
“…The overall low health status based on HPLP-II is consistent with previous study. [28][29][30][31][32] According to this study, medical students are not adopting health promoting lifestyle behaviours on daily basis and their life-style behaviours is disturbingly low.…”
Section: Discussionmentioning
confidence: 99%
“…Interpersonal relation took the second rank, but physical activity was the lowest one. Some studies carried in our country and other countries also showed that university students have low scores on physical activity sub domain [20] [22] [25]- [28]. The suggested explanation of this result may be that In Jordan, the commitment to physical activity programs still little, moreover, it is not easy to access exercise centers, and in addition to that the economic factor may be contributed to this finding as most of sport centers charge moderate to high fees.…”
Section: Discussionmentioning
confidence: 99%
“…In Jordan, previous study conducted by Haddad et al (2004) [20] revealed that first year nursing students obtained low score in Health Promotion Lifestyle Profile (HPLP) subscales and differed significantly in the three subscales of health responsibility, physical activity, and interpersonal relations; from first year Canadian nursing students. Another Jordanian study by Ammouri (2008) [21] revealed that a small percentage of Jordanian adults participated in health promoting behaviors and that demographic factors such as gender, age, and income are important determinant of the individual engagement in the health promoting behaviour.…”
Section: Introductionmentioning
confidence: 99%